2022
DOI: 10.3390/ijerph19042178
|View full text |Cite
|
Sign up to set email alerts
|

Functional Capacity of Tai Chi-Practicing Elderly People

Abstract: Research shows that ageing is modifiable or modulable, attending to external modifications and lifestyle factors: physical activity has a unique contribution to functional health and energy balance. Extensive research shows Tai Chi (TC) produced a major physical condition. To determine the impact of lifestyle on functional capacity, comparing the impact of continued long-life practice. Methods: 113 individuals (±71.53 years old): (a) PTC (n = 27); senior competitors, life-long training; (b) TC (n = 27); ±4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Niño et al (2022) confirmed that the aging process could slow down as a consequence of two external factors: doing more physical activity and changes in lifestyle, for example, spending less time on sedentary behaviors. In addition, the authors have indicated that practicing Tai Chi can help older people achieve both more comfortably.…”
Section: Theoretical Frameworkmentioning
confidence: 74%
“…Niño et al (2022) confirmed that the aging process could slow down as a consequence of two external factors: doing more physical activity and changes in lifestyle, for example, spending less time on sedentary behaviors. In addition, the authors have indicated that practicing Tai Chi can help older people achieve both more comfortably.…”
Section: Theoretical Frameworkmentioning
confidence: 74%
“…Beberapa hasil penelitian menyatakan bahwa penurunan kapasitas fungsional lansia dapat distabilkan atau dikurangi, tetapi tidak dapat pulih kembali (Palestin & B, 2013). Beberapa penelitian mengungkapkan bahwa kegiatan fisik dan program olahraga penting sebagai kebiasaan hidup sehat serta sangat berkontribusi terhadap kesehatan dan peningkatan kapasitas fungsional masyarakat lanjut (Niño et al, 2022) Latihan fisik merupakan cara yang paling baik dalam meningkatkan kapasitas fungsional dan kualitas hidup lansia (Marandini et al, 2017).…”
Section: A Latar Belakangunclassified
“…An open-label, randomized controlled trial (YOFEAR trial) assessing the effect of yoga therapy in elderly patients (≥60 years) with fear of falling using standardized scales is being carried out in a tertiary hospital in Northern India, with results awaited [19]. Tai chi also improves balance and reduces falls in the elderly population [20][21][22]. Similarly, studies evaluating the benefits of Qigong in elderly patients have reported favorable results [23][24][25][26].…”
mentioning
confidence: 99%